Social Finance and Social Enterprises: A New Frontier for Development in Indonesia - David Soukhasing; Valencia Dea; Christie Ruslim (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2017)
The number of social finances and social enterprises are steadily growing in Indonesia. However, there is yet to be comprehensive research in this context. The objective of this study is to explore and identify the unique challenges of social investment in Indonesia. There are three key players in social investment ecosystem in Indonesia. Social enterprises, which aim to solve social or environmental problems, are mostly at their early stage and not investment ready. Meanwhile, many investors, with or without intention to invest for social mission, are not willing to fund early-stage enterprises. There are also challenges or false perceptions from traditional financial institutions in giving external funding to social enterprises. Enablers act as catalysts for the growth of social enterprises; however, their presence in Indonesia received an equivocal review, as many of them are lacking instruments as a social enterprise enabler. Blended finance is explored to be the solution to the unmet demand and supply of funding. There are two tools to implement blended finance model. With direct funding scheme, investors are given guarantees in exchange for the higher risks of investing in seed- and growth-stage social enterprises. Alternatively, support mechanisms acknowledge and address different issues in every lifecycle through various building capacity and programs.